Writing Kakawihan as a Local Wisdom's Teaching Material in Grade VII SMPN 3 Cianjur - Tita Herdila (Universitas Suryakanca, 2018)
This paper is motivated by the lack of students' interest in learning to write poetry and lack of interest in literature. In addition, teaching materials based on local wisdom are still rarely used in learning Indonesian. In connection with this, this paper will describe the utilization of the skills and abilities of students in writing poetry. The method used in the research is descriptive. The research technique used is content analysis, interviews, and tests. Based on the results of the study, it can be seen that the average value of kakawihan's poetry writing ability in class VII of SMP N 3 Cianjur is 77.9 is in a good category with 76-85 mastery interval. The highest score of students in writing kakawihan poetry is 87 obtained by one student (4%), and the lowest value is 73 obtained by 5 students (20%). Thus, kakawihan kaulinan barudak can be used as teaching material in learning Indonesian language based on local wisdom.Keywords: writing poetry, kakawihan kaulinan barudak